1986
DOI: 10.1073/pnas.83.16.6048
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis of the Ha-ras oncogene in mouse skin tumors induced by polycyclic aromatic hydrocarbons.

Abstract: The importance of mutational activation of the Ha-ras protooncogene in polycyclic aromatic hydrocarboninduced mouse skin tumors was investigated in a complete carcinogenesis model using repetitive applications of 7,12-dimethylbenz [a]anthracene (DMBA), or in an initiation-promotion model using a single application of dibenz [c,h] an early event in skin carcinogenesis. Thus, mutation of the 61st codon of the Ha-ras-1 gene appears to be a critical step in the formation of mouse skin tumors induced in both of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
124
2
1

Year Published

1989
1989
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(137 citation statements)
references
References 26 publications
10
124
2
1
Order By: Relevance
“…It has been postulated that the malignant conversion of the benign papillomas occurs as a result of somatic mutations in the expanded population of initiated cells (Moolgavkar and Knudson, 1981;Potter, 1981). Initiation of tumorigenesis by the carcinogen 7,12-dimethylbenz[a]anthracene (DMBA) induces a speci®c point mutation at codon 61 of the Ha-ras-1 gene (Balmain and Pragnell, 1983;Bizub et al, 1986;Roop et al, 1986). Histopathological and cytogenetic studies demonstrated that relevant changes occur during papilloma progression.…”
Section: Introductionmentioning
confidence: 99%
“…It has been postulated that the malignant conversion of the benign papillomas occurs as a result of somatic mutations in the expanded population of initiated cells (Moolgavkar and Knudson, 1981;Potter, 1981). Initiation of tumorigenesis by the carcinogen 7,12-dimethylbenz[a]anthracene (DMBA) induces a speci®c point mutation at codon 61 of the Ha-ras-1 gene (Balmain and Pragnell, 1983;Bizub et al, 1986;Roop et al, 1986). Histopathological and cytogenetic studies demonstrated that relevant changes occur during papilloma progression.…”
Section: Introductionmentioning
confidence: 99%
“…24 In correlation with this, a relatively high incidence of the mutated Ha-ras oncogene has been found in keratoacanthomas from both human and experimental models, 5,10 and in human and animal cutaneous SCC. 16,[25][26][27] These findings further suggest that ras oncogenes play important roles in all steps of tumor initiation, regression, and progression, and that additional cellular factors appear to be involved in the malignant progression. However, the mechanisms of the rasrelated regression of keratoacanthoma and progression of SCC are still not well understood.…”
mentioning
confidence: 97%
“…This leads to a specific activating A<T mutation at codon 61 of the H-ras gene in virtually all DMBAinitiated tumours. 15,16 However, the same target gene is mutated, albeit by a different mechanism, when alternative mutagens are used for chemical initiation of mouse skin. Both methyl-nitrosourea (MNU) 17 and alkylating agents 18 result in activating G<A transitions at codon 12 of H-ras.…”
Section: Initiating Events In Tumourigenesismentioning
confidence: 99%